Taxation and International Migration of Superstars: Evidence from the European Football Market - Kleven, Henrik Jacobsen; Landais, Camille; Saez, Emmanuel (American Economic Review, 2013)
We analyze the effects of top tax rates on international migration of football players in 14 European countries since 1985. Both country case studies and multinomial regressions show evidence of strong mobility responses to tax rates, with an elasticity of the number of foreign (domestic) players to the net-of-tax rate around one (around 0.15). We also find evidence of sorting effects (low taxes attract highability players who displace low-ability players) and displacement effects (low taxes on foreigners displace domestic players). Those results can be rationalized in a simple model of migration and taxation with rigid labor demand. (JEL F22, H24, H31, J44, J61, L83)